Evaluation of Demographic, Histopathologic and Radiological Features of Thyroid Cancer Patients (Annals of Medical Research, 2021)
Aim: Our aim of this retrospective study was to evaluate the demographic, histopathologic and radiological features of thyroid cancer patients.
Keywords: Thyroid Cancer; Patients; Demography; Histopathology; Epidemiology; Ultrasonography.